Profil Pembelajaran Mahasiswa Berbasis E-Learning Pada Prodi Ilmu Komunikasi STAHN Mpu Kuturan Singaraja - Wayan Supada (Pramana: Jurnal Hasil Penelitian, 2021)
In the implementation process, several positive and negative phenomena were found in the implementation of the online or online lecture system carried out by universities. The readiness of lecturers and students is required to be adaptive so that the learning process can run well. This research was conducted to determine the profile of online learning as a study and evaluation material in the implementation of lectures. The research population was all students of the communication science study program, totaling 259 people. The data collection technique used a questionnaire which was distributed to all students. For data analysis techniques using quantitative descriptive analysis. The results showed that the learning profile based on the variables studied showed that there were several things that needed to be evaluated and improved. Meanwhile, several aspects that become the main concern to be implemented are structural, ability to motivate students, task completion, synthesis and time efficiency.